Effect of Environmental Stimuli and Social Factors Against Impulsive Buying Tendency: Emotions Positive as a Mediation Variable (Case Study on Indomart Consumers in Banda Aceh) - YUSUF, Zulfan (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2021)
This study aims to analyze the effect of environmental stimuli and social factors against impulsive buying tendency case study on Indomart consumers in Banda Aceh. The data analysis method used in this study was through data quality testing to determine the validity of each question item. Furthermore, hypothesis testing is carried out using the path analysis test tool. Based on the results of the research and discussion, it is known that the conclusions of the study are 1) The influence of environmental stimuli has a significant effect on positive emotions in Indomart Superstore consumers in Banda Aceh, 2) Social factors have a significant effect on positive emotions in Indomart Superstore consumer products in Banda Aceh, 3 ) Environmental stimuli have a significant negative effect on impulse buying at the Indomart Superstore in Banda Aceh, 4) The influence of social factors has a significant effect on impulse purchases at Indomart Superstore in Banda Aceh, 5) The influence of positive emotions has a significant effect on impulsive buying at the Indomart Superstore in the city Banda Aceh, 6) Positive emotions mediate environmental stimuli to impulse buying at Indomart Superstore in Banda Aceh city, and 7) Positive emotions mediate social factors to impulsive buying at Suzuya Superstore in Banda Aceh City.